EFFECTS OF EXPOSURE TIME IN A FLANKER TASK FOR DIFFERENT CONDITIONS OF TARGET-FLANKER DISTANCE - García Sevilla, Julia; Pedraja Linares, María José; Campoy Menéndez, Guillermo; Egea-Caparrós, Damián Amaro; Martín Oviedo, Pedro; Montoro Martínez, Pedro Raúl (Anales de Psicología / Annals of Psychology, 2003)
The aim of our research is to assess the effect of exposure time of stimuli on the magnitude of the Flanker Compatibility Effect (FCE). Therefore, we have carried out an experiment which different exposure time conditions (14 ms, 157 ms and until response) related to different spatial distance conditions (0’16º, 0,47º, y 1,14º of visual angle center to center). The results suggest that exposure time does not affect the FCE, even under different spatial distance conditions. We conclude that possibly a certain degree of automaticity in the processing of the flankers takes place.